Experimental and numerical analysis of short sisal fiber-cement composites produced with recycled matrix - Lima, Paulo Roberto Lopes (2019)
The proper use of renewable or recycled source materials can contribute significantly to reducing the environmental impact of construction industry. In this work, cement based composites reinforced with natural fibers were developed and their mechanical behavior was characterized. To ensure the composite sustainability and durability, the ordinary Portland cement matrix was modified by adding metakaolin and the natural aggregate was substituted by 10% and 20% of recycled concrete aggregate. Compression and splitting tensile tests indicated that mechanical strength did not seem to be affected by recycled content. Flat sheets were cast in a self-compacted cement matrix and bending tests were performed to determine the first crack, postpeak strength and cracking behavior of the composites. The use of short sisal fiber as reinforcement of recycled cement matrices results in a composite with multiple cracking and increment of strength after first crack. The modeling of composites using finite element method allowed to determine the tensile stress-strain behavior of material and to design possible applications of this new sustainable material.